2023
DOI: 10.1002/dc.25112
|View full text |Cite
|
Sign up to set email alerts
|

Cytological study of 44 cases with solid papillary carcinoma and a systemic review of solid papillary carcinoma and neuroendocrine tumor of the breast

Abstract: Background: Solid-papillary carcinoma (SPC) of the breast is a rare variant of lowgrade in situ and invasive carcinoma but there are only a few of the cytologic studies. Methods:We examined 44 cases of SPC of the breast to define the cytologic features. We also made a systemic review of reported cases of SPC and neuroendocrine tumor (NET) of the breast.Results: Both of our and the reviewed cases with SPC were very similar in the cytologic finding. It included hypercellularity, highly discohesive clusters, nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…TCCRP shows characteristic nuclear findings, including nuclear grooves and intranuclear cytoplasmic inclusions. Yamada et al [9] reported that the nuclear chromatin in SPC was often salt-and-pepper-like, reflecting its neuroendocrine phenotype. The finding of salt-and-pepper-like chromatin was completely absent in our present patient with TCCRP.…”
Section: Discussionmentioning
confidence: 99%
“…TCCRP shows characteristic nuclear findings, including nuclear grooves and intranuclear cytoplasmic inclusions. Yamada et al [9] reported that the nuclear chromatin in SPC was often salt-and-pepper-like, reflecting its neuroendocrine phenotype. The finding of salt-and-pepper-like chromatin was completely absent in our present patient with TCCRP.…”
Section: Discussionmentioning
confidence: 99%
“…The cells are quite fragile and crush artifact is a common feature in biopsy specimens. Supporting the contention that cell carcinomas arise from a multipotential basilar epithelial cell, these tumors are often associated with an in situ and/or invasive carcinoma more typical for the site of origin [48][49][50]. Tumor cells show scant cytoplasmic organelles with occasional elongated cytoplasmic processes, sparse neurosecretory granules, and scattered poorly formed intercellular desmosomes [51,52].…”
Section: Structure Diagnosismentioning
confidence: 99%